Fabricating tiny oil droplets via reversible superwetting transition method and associated surface interaction mechanism. Issue 1 (22nd December 2022) - Qiao, Chenyu; Zeng, Hongbo
Abstract : Schematics of (a) wetting and (b) dispensing processes during producing tiny droplets with a fibril dispersing system, which are governed by the various intermolecular and surface forces involved.